Regional Labor Mobility in Spain - Liu, Lucy Qian. (Washington, D.C. : International Monetary Fund, 2018)
This paper studies the main factors that explain the low regional mobility in Spain, with a view to identifying policy options at the regional and central level to promote labor mobility. The empirical analysis finds that house prices, labor market conditions, and the pervasiveness of labor market duality at the regional level are the main determinants for Spain's regional mobility, while labor market institutions and policies play an important role at the national level. Policies that facilitate wage setting flexibility and reduce labor market duality could help enhance the functioning of the labor market, thereby promoting labor mobility. There may be also room for policies to incentivize people to move and provide support through targeted active labor market policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Geographic Labor Mobility; Immigrant Workers